Anti-inflammatory, Antipyretic, and Antinociceptive Effects of a Cressa cretica Aqueous Extract - Abdallah, Heba Mohammed Ibrahim; Elshamy, Abdelsamed Ibrahim; El Gendy, Abd El-Nasser Gaber; Abd El-Gawad, Ahmed Mohamed; Omer, Elsayed Abouelfotowh; De Leo, Marinella; Pistelli, Luisa (Planta Medica, 2017)
Cressa cretica is a widely grown halophytic plant traditionally used for the treatment of different ailments. Previous investigations reported its biological activity on a wide spectrum of diseases. In this study, in vivo antinociceptive, anti-inflammatory, and antipyretic activities of C. cretica aqueous extract whole plant were evaluated. In addition, the total polyphenol content, the total flavonoid content, and the chemical characterization of the extract were performed. C. cretica showed writhing inhibition in acetic acid-induced peripheral nociception of 43 and 48 % at doses of 50 and 100 mg/kg, respectively. The same doses increased latency time in a hot plate model of central analgesia by 66 and 78 % compared to the control group, respectively. The acute anti-inflammatory effect of the extract was explored in the carrageenan-induced rat hind paw test. The inhibition of paw volume was better than that of the standard drug indomethacin. C. cretica significantly decreased rectal temperature in the rats injected with Brewerʼs yeast. C. cretica aqueous extract showed both central and peripheral antinociceptive activities and was effective as an anti-inflammatory and antipyretic. Phenolic compounds, including chlorogenic acids and flavonol glycosides, were identified by HPLC-PDA-ESI-MS techniques. These findings indicate the medicinal importance of this traditionally used plant as a therapeutic remedy for different ailments.
Keywords: Cressa cretica; Convolvulaceae; anti-inflammatory; antinociceptive; antipyretic; chlorogenic acids; flavonol glycosides